The regulatory effect of blood group on ferritin levels in aging: a retrospective study - Ni Xiaolin; Fenghong Yao; Mingkang Pan (PeerJ)
Background Ferritin plays a pivotal role in the ageing process. Previous studies have identified statistically significant differences in ferritin levels among various ABO blood groups. However, the interaction between the ABO blood group and ferritin levels during senescence remains underexplored. Methods This research was conducted as a retrospective study involving a cohort of 3,843 individuals aged 40 and over who underwent blood type and ferritin testing at Beijing Zhongguancun Hospital. Assumption testing is employed to assess the normal distribution of continuous variables in the context of regression analysis. Spearman correlation analysis was employed to examine the relationship between the non-normally distributed biochemical indicators and ferritin levels. Age was considered the independent variable, while gender and biochemical indicators related to ferritin served as control variables. Blood type was analyzed as a moderating factor to evaluate its impact on the relationship between age and ferritin levels. Results Our findings revealed a negative correlation between ferritin and age (ρ =  − 0.099, p < 0.001). Significant differences in ferritin levels were observed between genders (p = 0.005) and blood groups (p < 0.001). The influence of age on ferritin levels varied across different blood groups, particularly in individuals with blood types A (p = 0.003, β =  − 0.072) and B (p < 0.001, β =  − 0.110), where the negative association between age and ferritin was more pronounced. Conclusion ABO blood type may influence ferritin levels as individuals age. Notably, in individuals with blood types A and B, the inverse relationship between age and ferritin levels was particularly significant among middle-aged and elderly individuals. These findings suggested the potential benefit of targeted iron supplementation for this population.